Design and experimental study of a low-temperature Stirling engine model - Baiman, G.B.; Pazylova, D.T.; Баубекова, Г.М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2026)
The aim of this paper is to study the physical principles of a low-temperature Stirling engine and develop a working model. Both ideal and realistic cycle parameters are considered. Actual energy losses occurring during engine operation are analyzed, and approaches for accounting for them in modeling are proposed, facilitating theoretical research on low-temperature heat engines. Various Stirling engine modifications are also considered, and their potential efficiency is analyzed depending on temperature, material properties, and operating conditions. The construction of an experimental engine model contributes to a deeper understanding of the mechanisms of heat transfer and energy conversion in closed cycles, which is important for the development of heat engine theory. Experimental research also contributes to the development of a domestic scientific base in the field of alternative energy. The study makes an educational and methodological contribution: a model has been proposed that can be used to clearly demonstrate the operation of a Stirling engine and conduct basic experiments, making it a useful tool in educational practice.